Cultural Diversities and Collective Rights - Mesić, Milan (2006)
The paper presents the controversy over the question wheter or not collective (group) rights can exist, in particualar as human rights, within a liberal concept of human rights. It discusses the various examples of already established collective (cultural) rights in individual Western countries.